Results and performances of X-ray imaging GEM cameras on FTU (1-D), KSTAR (2-D) and progresses of future experimental set up on W7-X and EAST Facilities. (18th October 2017) - Cordella, F.; Choe, W.; Claps, G.; Gabellieri, L.; Jang, J.; Jeon, T.; Lee, S.H.; Li, E.; Pacella, D.; Romano, A.; Song, I.
Abstract: The triple Gas Electron Multiplier (GEM) is a good candidate for the observation of the plasma volume emitting X-rays photons in the energy band up to 30 keV . The GEM camera system can be simply installed outside the port of a fusion device and it's a micropattern proportional gas detector which consists of an ionization gap, where X-rays photon conversion occurs, three consecutive foils working as amplification stage and finally a dedicated printed circuit board. Its simple experimental setup can be made in different configurations with 1D or 2D imaging possibilities: perpendicular GEM camera allows a 1D emissivity profile reconstruction instead a tangential GEM camera allows a poloidal cross-section image. Moreover, they offer high sensitivity, noise free, optical flexibility (zooming and tilting, magnification 10× × up to 30× × ), high contrast, high dynamic range (6 orders of magnitude) and good time resolution (submillisecond). In this work several experimental results already observed on the Frascati Tokamak Upgrade (FTU) and the Korean Superconducting Tokamak Advanced Research (KSTAR) devices will be presented. The perpendicular installation on FTU allows a 1D radial profile with 128 lines of sight, while thanks to the 2D tangential view of the plasma, the reconstruction of the cross section has been done on KSTAR. Between them there are dynamic and precursors of sawtooth, effects of Edge Localized Mode (ELM) in the core and possible interplay between core and edge in ELMs (high m modes), effects of plasma rotation in the core, dynamic of injected impurities in the outer part of the plasma or also impurity accumulation and localized effects of additional heating. Installation of GEM systems is planned on Wendelstein 7-X (W7-X) and the Experimental Advanced Superconducting Tokamak (EAST) also for their robustness and flexibility X-rays detection in presence of high radiative environments (neutrons and gammas). In future applications on the above mentioned fusion devices, another possibility under evaluation is to use standard tomographic methods using two orthogonal GEM camera systems.